Migration and Remittances : Recent Developments and Outlook - World Bank Group (World Bank, Washington, DC, 2017)
This Migration and Development Brief reports global trends in migration and remittance flows, major policy developments, and the Sustainable Development Goal (SDG) indicators for reducing remittance costs and recruitment costs. The Brief reports new data on recruitment costs, a potential indicator for the SDG of promoting safe and regular migration. The special focus of the Brief is return migration, currently a challenging issue globally following the increase in asylum seekers and undocumented migrants.